Author: Sari Dewi PENGARUH MORAL PAJAK, STRATEGI BERBASIS KEPERCAYAAN, AMNESTI PAJAK, DAN KESADARAN PAJAK TERHADAP KEPATUHAN WAJIB PAJAK: STUDI EMPIRIS DI INDONESIA : A Study on the Impact of Tax Morale, Trust-Based Strategy, Tax Amnesty, and Tax Awareness on Tax Compliance: Evidence from Indonesia - Sari Dewi; Sanjaya, Daffa Salsabilla (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2025)
This study aims to understand the key factors influencing tax compliance in Indonesia by highlighting four important aspects: tax morale, trust-based strategies, tax amnesty, and tax awareness. This research adopts a quantitative approach using primary data collected through questionnaires. Data collection was conducted using the snowball sampling method, and data analysis was performed using the Partial Least Squares (PLS) method. The findings indicate that tax morale and trust in the government significantly influence tax compliance. Meanwhile, the tax amnesty program has a positive impact, though it is not yet sufficient to significantly improve overall compliance. Additionally, increasing tax awareness has been proven to contribute substantially to taxpayer compliance. These findings emphasize the importance of tax education, particularly for MSMEs in Batam, to enhance their understanding of tax obligations. This study provides a new perspective on tax compliance in Indonesia. With the right policy approach, tax compliance can be sustainably improved to support national economic development. Abstracts must follow the format outlined below and there must always be the following four sub-headings and their accompanying explanations. This study examines key factors influencing tax compliance in Indonesia, focusing on tax morale, trust-based strategies, tax amnesty, and tax awareness. It aims to address low tax compliance, a challenge in optimizing government revenue. A quantitative approach was used with primary data collected through questionnaires via snowball sampling, targeting MSMEs in Batam. Data were analyzed using the Partial Least Squares (PLS) method to assess relationships between variables. Tax morale and trust in the government significantly impact tax compliance. While tax amnesty has a positive effect, it is not yet sufficient to boost overall compliance. Increased tax awareness contributes to better taxpayer behavior. The study highlights the need for tax education and trust-building measures. Authorities should prioritize awareness programs, especially for MSMEs, to improve compliance. Long-term strategies should focus on sustainable policies to enhance voluntary tax compliance and support economic growth.